Pengaruh behavior skill training terhadap interaksi sosial korban bullying di SMP N 1 Kaligondang kabupaten Purbalingga - Bunga Nafingah, Ade Ayu; Suroso, Jebul (Jurnal Keperawatan Muhammadiyah, 2020)
INFORMASIABSTRACTKorespondensi:Injeso@yahoo.com        Keywords:bullying, social interaction, behaviour skill, trainingObjective: Identifying the effect of behaviour skill training on the social interaction of bullying victims in SMPN 1 Kaligondang, Purbalingga Regency Method: This research is quantitative research of pre-experimental design (one group pre-test post-test design). The sample consists of 30 bullying victim students in SMPN 1 Kaligondang taken through total sampling. The research instruments are olweus bully/victim revised questionnaire and social interaction ability questionnaire with the test of paired sample t-testResults: Most of the respondents are male, 16 respondents, (53.3%) and 14 respondents are female (46.7%) with the age of 12-15 years old. There are 12 respondents in grade 7 (40%) and 9 respondents in grade 8 and 9 respondents in grade 9 (30%). The average scores of pre-test and post-test are 86.63 and 104.07. Moreover, the result of Sig. (2 tailed) p-value is (0.000 0.05).Conclusion: There is significant difference between the result of pre-test and post-test. Moreover, it is found that there is an effect of behaviour skill training on the social interaction of bullying victims